Remuneration and Discipline of Employees in Private Universities in Uganda - Azabo, Emurugat Immaculate; Gaite, Sofia Sol; Anumaka, Blessing Ijeoma; Wunti, Yakubu Ibrahim (Advances in Social Sciences Research Journal, 2020)
The study analyzed the relationship between remuneration and discipline of employees in private universities in Uganda. It involved 385 respondents from seven private chartered and accredited universities. Data was collected using a self-administered questionnaire whose validity and reliability was confirmed through Factor Analysis and Cronbach Alpha test. Descriptive analysis involved the use of means, while Pearson Linear Correlation Coefficient was used to test the hypothesis. The results revealed that remuneration was a positive significant determinant of discipline of employees. In conclusion remuneration was an important element in that it influenced the discipline of employees in private universities. It was recommended that managers of Organisations such as private universities should put emphasis on their remuneration strategies which will influence the discipline of their employees and thus their rentation.